2010
DOI: 10.2188/jea.je20090054
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Subjective Sleep Assessment Tools for Healthy Preschool Children: A Comparative Study Between Sleep Logs, Questionnaires, and Actigraphy

Abstract: BackgroundSleep pattern is an important factor in a child’s mental, behavioural and physical status. To evaluate the sleep patterns of children, subjective tools such as sleep logs and questionnaires are still widely used in addition to objective methods of sleep assessment. Despite the established correlation between subjective and objective sleep variables, the characteristic features of subjective assessment have not been elucidated.MethodsTo investigate the characteristics of parental sleep assessment (dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 26 publications
(32 reference statements)
9
118
3
Order By: Relevance
“…However, proxy-reporting may have introduced recall and social desirability bias. [41][42][43] Further research is needed to explore comprehensive lifestyle behaviour patterns used in objective measurements. Third, socioeconomic status, such as parents' educational level and/or household economic level, might affect the children's overweight and behaviours, but our study could not include these kinds of variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, proxy-reporting may have introduced recall and social desirability bias. [41][42][43] Further research is needed to explore comprehensive lifestyle behaviour patterns used in objective measurements. Third, socioeconomic status, such as parents' educational level and/or household economic level, might affect the children's overweight and behaviours, but our study could not include these kinds of variables.…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by the use of self-reported information. While parental report of sleep duration is shown to be highly correlated with objective measures among pre-school children, 30 it has also been shown to overestimate sleep duration by up to 50 minutes among school-aged children. 31 Nevertheless, validated measures for dietary intake 15 and physical activity 18 were used to minimize potential bias.…”
Section: -423mentioning
confidence: 98%
“…Parent report reflects parent concern about a child's sleep, which in turn is likely to be the motivator for parents who seek help from a program such as this. 31,46 Parents were the main source of outcomes data and could not be blinded, so bias could explain our positive findings; as noted above, we were not able to objectively reassess learning at 12 months because of our limited resources. It is not known whether existing school-based health professionals, such as school nurses in Australia, can effectively deliver this intervention with at least the same efficacy.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Report of a moderate/severe sleep problem determined the child's trial eligibility. We used caregiver report because (1) parent perception of a sleep problem is a key driver of help-seeking behavior, (2) the definition of what constitutes a sleep problem from a research perspective remains a hotly debated topic, 30 (3) subjective measures are more cost-effective and feasible to use than objective measures for determination of child sleep problems in large population-based settings, 31 and (4) parent report captures behavioral bedtime problems better than actigraphy.…”
Section: Primary Outcome Measurementioning
confidence: 99%